Pembelajaran Project-Based Learning dalam Meningkatkan Berpikir Kritis Siswa - Lin Herlina; Mega Triasya Remana; Mila Andriani Nurcahya; Prihantini (Bidayatuna, 2022)
Success in learning is always related to the role of educators in achieving national education goals. The application of project-based learning is the right step so that national education goals can be achieved. This project-based learning can train and improve skills in critical thinking. Critical thinking is critical in the learning process and future life. This study aimed to determine whether the application of project-based learning affects students' critical thinking levels. The research method used in this study is a qualitative method and a descriptive approach. Data were collected by conducting surveys and interviews with students and teachers of class V SD No. 8 Benoa. The research results obtained showed that students' critical thinking could be improved by implementing project-based learning. This is because, through various projects, students must carry out a process of brainstorming to complete the project. So with this, students can have increased critical thinking skills by making projects, especially those based on a problem